2021
DOI: 10.1016/j.heliyon.2021.e07818
|View full text |Cite
|
Sign up to set email alerts
|

Comparing radiological presentations of first and second strains of COVID-19 infections in a low-resource country

Abstract: Introduction The novel corona virus popularly referred to as COVID-19 disease and SARS-CoV-2 was first detected in Wuhan, China in December 2019. It was declared a pandemic by the World Health Organization (WHO) on March 11, 2020. In Ghana, the first two cases of COVID-19 infection were recorded on March 13, 2020 with a strain imported from Europe. In December 2020, a new strain from South Africa was detected in Ghana which was associated with higher transmission rates, severity of the disease, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…This is supported by Figure 3, which compares mortality between waves I and II. This also is consistent with studies that found a new strain of the virus caused more severe infections, as evidenced by abnormal CXR [36][37][38][39]. This cohort included patients with moderate to severe COVID-19, with 76% being oxygen dependent and 78% receiving corticosteroid therapy.…”
Section: Discussionsupporting
confidence: 87%
“…This is supported by Figure 3, which compares mortality between waves I and II. This also is consistent with studies that found a new strain of the virus caused more severe infections, as evidenced by abnormal CXR [36][37][38][39]. This cohort included patients with moderate to severe COVID-19, with 76% being oxygen dependent and 78% receiving corticosteroid therapy.…”
Section: Discussionsupporting
confidence: 87%
“…However, as regards the severity of CT lung affection in different age groups, we found that there was a positive moderate correlation between age and total CT severity score of the lung in the first wave (r=0.51, p-value<0.001), while a significant positive mild correlation in the second wave ( r=0.31 and p-value <0.001), and this is not matching with results of E.K.K. Brakohiapa et al study may be due to different sample sizes as well as different environmental and ambient conditions between the two studies (15) . According to CORADS classification, we found that CORADS 3 with typical CT findings was the most common type in all patients (43.8%, and 49.4%) and most normal patients with CORADS 0 were in young age group A (≤ 30 years) by (12.8% and 22.6%) in both first and second waves respectively.…”
Section: Tablesmentioning
confidence: 65%
“…[44][45][46] While the rates of severe disease may vary between strains, the pulmonary complications and their radiological manifestations appear to be consistent. 47 Also, these are indeed shared by other causes of viral pneumonia. 5 6 In one study comparing chest CT findings in patients infected with different variants of COVID-19, while there was a difference in the severity of radiological findings, the nature and distribution of changes was similar.…”
Section: Discussionmentioning
confidence: 98%